15. STATUS OF MAINTAINING GOOD PRACTICE STANDARDS FOR DRUG RETAIL FACILITIES IN HANOI CITY IN 2024 (Vietnam Journal of Community Medicine, 2025)
ABSTRACTObjective: To assess the status of maintaining Good Pharmacy Practice (GPP) standards at private pharmacy retail establishments with GPP certification in Hanoi city in 2024.Subjects and methods: Cross-sectional study at 362 private pharmacy retail establishments with GPP certification in Hanoi city, including 198 pharmacies and 164 randomly selected drugstores. Data were collected through a survey based on 19 GPP criteria according to Circular 02/2018/TT-BYT and analyzed using Stata 13.0 software.Results: The rate of non-compliance with GPP criteria was high, especially in pharmacies (73.74%) compared to drug counters (19.51%). Principal areas of concern included inadequate staff training (69.14% in pharmacies, 97.69% in drugstores), absence of dedicated counseling areas (95.06% in pharmacies, 98.02% in drugstores), and lack of periodic quality control measures (67.90% in pharmacies, 57.10% in drugstores).Conclusion: These findings highlight the persistent challenges in maintaining GPP standards across most retail outlets in Hanoi, underscoring the necessity for enhanced training initiatives, strengthened regulatory oversight, and improved operational management to ensure sustained compliance.
Keywords: Retail pharmacy, GPP, good pharmacy practice, Hanoi